TAAT builds resilience for maize productivity through scale out of Fortenza Duo seed treatment technology: TAAT news Vol. 2 - Technologies for African Agricultural Transformation (Technologies for African Agricultural Transformation, 2019)
The African Development Bank launched the Technologies for African Agriculture Transformation (TAAT) programme as part of the Bank’s Feed Africa strategy that is harnessing elite scientific research/technologies and disseminating at scale to African farmers. TAAT’s main objective is to improve the business of agriculture across Africa by raising agricultural productivity, mitigating risks and promoting diversification and processing in 18 agricultural value chains within eight Priority Intervention Areas (PIA). The programme increases agricultural productivity through the deployment of proven and high-performance agricultural technologies at scale along selected value chains which include cassava.